Electrocardiographic Evaluation of Xylazine-Etomidate Isoflurane and Dexmedetomidine-Ketamine-Isoflurane Anaesthesia under Guaifenesin Premedication for Various Surgeries in Cattle - Ramya , N M; Bhagavantappa, B; Shivaprakash; Kumar, D Dilip; Venkatgiri; Kumar, M Vijay; Mehdi, Ghulam (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The clinical study on electrocardiographic evaluationof two modalities of general anaesthesia was conducted in 12 clinical cases of cattle of either sex. The animals were randomly divided into two groups, consisting of 6 animals in each group. The cattle in both groups were premedicated with an intravenous injection of 50 mg/kg guaifenesin. The cattle in group-I were sedated with inj. xylazine (0.1 mg/kg I/V) and induced with inj. etomidate (0.5 mg/kg I/V). The cattle in group-II were sedated with inj. dexmedetomidine (2.5 µg/kg I/V) and induced with inj. ketamine (3 mg/kg I/V). Cattle from both groups were maintained under isoflurane anaesthesia. The morphological abnormalities were not detected in electrocardiography in cattle of any of the groups, except for changes in the amplitude and duration of the P wave, QRS complex, T wave, PR interval, and QT interval.